The Effect of Maternal Exercise Types on One Month Infant Resting Metabolic Rate - Clark, Ethan (East Carolina University)
PURPOSE: This thesis investigates the effects of maternal exercise types on infant resting metabolic rate (RMR). While extensive research supports the benefits of exercise in preventing chronic diseases such as cardiovascular disease and diabetes, there is limited understanding of how maternal exercise types affects infant whole-body metabolic outcomes. Given that the fetus is entirely dependent on maternal health and behavior, understanding how different types of prenatal exercise influence offspring metabolism is crucial. This study aims to examine the relationship between maternal exercise types, particularly resistance, aerobic, and combination training, and infant RMR. Previous research has primarily focused on maternal exercise effects on infant body composition, but the direct impact of maternal exercise types on RMR is unexplored. By addressing this gap, this research seeks to provide new insights into how prenatal exercise types can shape early metabolic function, potentially influencing long-term health outcomes. METHODS: This study examined the effects of prenatal exercise types on a one-month infant resting metabolic rate (RMR). Women ages 18-40 with singleton pregnancies, a pre-pregnancy BMI between 18.5-39.9 kg/m2, and gestational age <16 weeks were recruited. Participants were randomized to aerobic training (AT), combination (aerobic + resistance) training (CT), resistance training (RT), or an attention-control group. Exercise intensity was monitored via heart rate and the Borg scale. In the postnatal period, one-month infant RMR was measured using indirect calorimetry. Statistical analyses included ANOVA, Cohen’s d, and linear regression to assess group differences in RMR and explore predictors of one-month infant metabolism, respectively. RESULTS: Descriptive statistics provided an overview of participant characteristics, with no significant differences between exercise groups in demographic or perinatal variables (p > 0.05). ANOVA analyses revealed no differences in maternal or infant metrics, including BMI, birth weight, and growth parameters at one month (p > 0.05). Similarly, we found trends of differences in one-month infant resting metabolic rate (RMR) between exercise groups (RMR: F (3,24) = 2.463, p = 0.087). Moderate to large effect sizes, using Cohen’s D, were found in AT (D=0.75) and RT (D=0.68). Importantly, linear regression analysis identified significant increases in one-month infant RMR exposed to the resistance exercise in utero (p=0.0069), and significant decreases in one-month infants from women who performed aerobic training during pregnancy (p=0.0013), compared to the control. Additionally, pre-pregnancy BMI was positively associated with higher RMR (p=0.0006). The study limitations, mainly due to a small sample size, highlight the need for larger, more diverse research. CONCLUSION: This study suggests that prenatal exercise, specifically prenatal resistance exercise, augments infant RMR while aerobic training might attenuate infant RMR; these trends are worth further exploration. Overall, these findings support the potential benefits of resistance exercise during pregnancy for improved infant metabolic health.
Keywords: Health Sciences, Kinesiology